Strategy to Increase Sales of Deposit Products at Bank Sumut Syariah KCP Binjai - Batubara, Indah Wulan sari; Syarvina, Wahyu (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This research was made because of the increasing intense competition in the sale of Islamic banking products, both in terms of marketing and promotion so that it will have an effect on earning profits at PT Bank Sumut Syariah KCP Binjai. The formulation of the problem studied is what is the strategy to increase sales of Islamic banking products at PT Bank SUMUT Syariah and what are the strategies used in implementing sales of Islamic banking products to get maximum profit at PT Bank SUMUT Syariah. The purpose of this study is to improve the sales strategy of Islamic banking products in order to achieve maximum profit. The research conducted is descriptive qualitative research using field research methods, namely observations and interviews conducted by analyzing data sourced from the research location or place, namely regarding the Sales Strategy of Islamic Banking Products at PT. Bank SUMUT Syariah KCP Binjai. The results of the research obtained are the sales strategy of Islamic banking products used by PT Bank SUMUT Syariah, namely by socializing in the marketing or marketing department, both in distributing brochures, pamphlets, as well as holding socialization seminars both in schools and other agencies to achieve certain goals, namely achieve maximum profit.